(1)ab=cosθcosx+ sinθsinx=cos(x-θ)
bc=cosx sinθ+ sinx cosθ=sin(x+θ)
则令y=(ab)cosx+(bc)sinx= (cosθcosx+sinθsinx)* cosx+ (cosx sinθ+sinx cosθ)*sinx
=cosθcosx^2+ 2sinθsinx cosx+ cosθsinx ^2
=cosθ(cosx^2+sinx ^2)+ 2sinθsinx cosx
=cosθ+sinθsin2x,
函数过(π/6,1),代入得cosθ+sinθsin(2*π/6)=1,cosθ+sinθ*√3/2=1
cosθ+√(1-cosθ^2)*√3/2=1,√(1-cosθ^2)*√3/2=1- cosθ,
(1-cosθ^2)*3/4=1-2 cosθ+cosθ^2,
7cosθ^2-8cosθ+1=0,(cosθ-1)(7cosθ-1)=0,cosθ=1(舍),cosθ=1/7,
θ=arcos(1/7)≈81.7868°,
sinθ=4√3/7
(2)y=g(x)=1/7+4√3/7*sinx,
当x=0时,y=1/7,是最小值;
当x=π/2时,y= 1/7+4√3/7,是最大值